Development of Canva-Based Interactive Media in a Project-Based Learning Model to Improve the Cognitive Abilities of Vocational High School Students - Surya, Rizky Gheni Praba Surya; Sutopo, Yeri (Journal of Vocational and Career Education, 2024)
The teaching of Pancasila and Civic Education (PPKn) in Vocational High Schools (SMK) still faces challenges in delivering material that is engaging and easy to understand. The abstract nature of Pancasila values often makes them difficult to grasp without supportive media. The lack of interactive and digital-based learning media becomes a barrier to meaningful learning. Therefore, this study aims to develop Canva-based interactive learning media within a Project-Based Learning (PjBL) model to improve students’ cognitive abilities in PPKn subjects at SMK. This research is a type of Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The developed product is a digital interactive media using Canva, presenting Pancasila content visually, communicatively, and contextually. Validation was conducted by two media experts and three content experts. Practicality was tested through questionnaires to teachers, while effectiveness was evaluated using pretests and posttests in experimental and control classes. The implementation was carried out using a project-based learning approach. The results show that: (1) the media visualizes Pancasila values effectively and attractively; (2) expert validation confirms its feasibility with media expert CVI at 0.88 (PoA 88%) and content expert CVI at 0.91 (PoA 91%); (3) practicality is in the “very practical” category (average score 93.3%); and (4) effectiveness testing indicates a significant difference (t = 4.727; sig. = 0.000) and higher N-Gain in the experimental class. Therefore, Canva-based interactive media is feasible, practical, and effective for project-based PPKn learning in SMK.